1996
DOI: 10.1083/jcb.133.4.843
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cellular and subcellular patterns of expression imply distinct functions for the Drosophila homologues of moesin and the neurofibromatosis 2 tumor suppressor, merlin.

Abstract: Abstract. Interest in members of the protein 4.1 superfamily, which includes the ezrin-radixin-moesin (ERM) group, has been stimulated recently by the discovery that the human neurofibromatosis 2 (NF2) tumor suppressor gene encodes an ERM-like protein, merlin. Although many proteins in this family are thought to act by linking the actin-based cytoskeleton to transmembrane proteins, the cellular functions of merlin have not been defined. To investigate the cellular and developmental functions of these proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 44 publications
10
124
0
1
Order By: Relevance
“…The accumulation of Merlin at cell-to-cell junctions in confluent epithelial and endothelial cells [5,7], within lamellipodia in various types of cell [62][63][64], and on the surface of endocytic vesicles in Drosophila epithelial tissues [53,65] is consistent with this general hypothesis (Sidebar C).…”
Section: Merlin Localizationsupporting
confidence: 60%
“…The accumulation of Merlin at cell-to-cell junctions in confluent epithelial and endothelial cells [5,7], within lamellipodia in various types of cell [62][63][64], and on the surface of endocytic vesicles in Drosophila epithelial tissues [53,65] is consistent with this general hypothesis (Sidebar C).…”
Section: Merlin Localizationsupporting
confidence: 60%
“…Sequence analysis revealed that this gene represents the chick homolog of Nf2, a tumor suppressor gene, which had been identified previously in human (Rouleau et al, 1993;Trofatter et al, 1993), mouse (Haase et al, 1994;Claudio et al, 1994;Hara et al, 1994;Huynh et al, 1994), rat (Gutmann et al, 1995), and Drosophila (McCartney and Fehon, 1996). Analyses of the predicted amino acid sequence of c-merlin revealed protein domains in common with other identified merlin molecules ( Fig.…”
Section: Nf2 Cdna and Merlin Proteinsupporting
confidence: 52%
“…The Drosophila homolog of merlin shares sequence similarity to the human merlin protein (McCartney and Fehon, 1996;Fehon et al, 1997).…”
Section: Supplementary Notesmentioning
confidence: 99%
“…A phylogenetic study indicates that the FERM domains of ERM homologs from sea urchin, Caenorhabditis elegans, Drosophila melanogaster and vertebrates share 74-82% amino-acid identity and have about 60% identity with those of merlin [17,[28][29][30][31][32][33][34]. These levels of identity are exceptionally high, implying that the protein structure of the merlin and ERM proteins from these species may be well conserved.…”
Section: Caenorhabditis Elegansmentioning
confidence: 99%